EXPLORING EMOTIONAL INTELLIGENCE AND STUDENT WELLBEING IN MULTICULTURAL UNIVERSITY SETTINGS - Tasneem, Rokhiya; Vashisth, Vandana; Tanwar, Vimlesh (International Journal of Engineering Technologies and Management Research, 2025)
The major reason for this research was to find out the perception of college students who take part in multicultural programs regarding the relationship between EI, MA, and PWB. The study aimed at determining the extent to which the relation of EQ to mental health is influenced by intercultural adaptation. The participants in this research numbered 384 and were from very diverse intellectual and cultural backgrounds, while the methodological approach was a quantitative descriptive correlational one. The data was subjected to Structural Equation Modeling (SEM) to verify if our assumption was correct. The researchers utilized standardized scales to evaluate EI, MA, and PWB. The study showed that high EQ had a profound effect on mental health and adaptability to different cultures, thus it would be inferred that through having EQ, students could better regulate their feelings, recover quickly from their failures, and cooperate with people from different cultures. Furthermore, the capacity to blend in with different cultures has a positive effect on the individual’s emotional health through the activity of the most important outer character trait, which is the ability to mix with different cultures. The capacity to adapt to other cultures has a significant bearing on the correlation between EQ and mental health since it moderates the relationship between the two. University and college students can benefit from programs that teach them to be more resilient, accepting, and healthy by increasing their intercultural awareness and emotional intelligence, according to the study's authors. Not only did this study fill a need in our understanding of multicultural university environments, but it also provided evidence that intercultural adaptation is an important process connecting EQ to psychological health.